Pengembangan Bahan Ajar Menggunakan Model RME Berbasis Etnomatematis untuk Meningkatkan Kemampuan Literasi Numerasi - Ahmad Landong; Arrini Shabrina Anshor; Muhammad Tri Bintang; Dina Sri Novita; Mutiara Rahmah; Nurul Haliza Lubis; Silvia Silvia; Robiyatul Adawiyah Harahap; Tri Makhlisa; Mipta Mawardah; Mellisa Trulyn Ginting; Siti Aisyah (Lembaga Bale Literasi, 2025)
This study aims to develop mathematics teaching materials using the Realistic Mathematics Education (RME) model based on ethnomathematics to improve elementary school students’ numeracy literacy skills. The research method used is Research and Development (R&D) with the ADDIE model. The research subjects were fourth-grade students at SDN 067775 Medan Johor. The results show that the developed mathematics teaching materials using the ethnomathematics-based RME model achieved a very valid category, with average validation scores of 86.60% from teaching material experts, 88.30% from teaching module experts, and 89.06% from content experts. The numeracy literacy test obtained a validity score of 81.81%, resulting in an overall average validity score of 86.44%, categorized as very valid. The teaching materials also met the effectiveness criteria, with a student response questionnaire result of 94% and student absorption rate of 96.42%, yielding an average effectiveness score of 95.21%. Therefore, the ethnomathematics-based teaching materials using the RME model are considered effective. Furthermore, the practicality criterion was fulfilled, as shown by the lesson implementation observation sheet, which scored 93.54%, categorized as well-implemented. In conclusion, the developed teaching materials are valid, effective, and practical for use in learning and can improve students' numeracy literacy skills by 28%.